Affordable modifications for sustainable houses in urban informal settlements: a case study of Bandung, Indonesia. Issue 3 (2nd September 2021) - Parisi, Cristiana de Almeida; Kubota, Tetsu; Surahman, Usep
ABSTRACT: We investigated mould risk, TSP and PM2.5, and the self-reported prevalence of respiratory diseases in a typical unplanned urban residential neighbourhood (Kampung) in Bandung, Indonesia during 2018–2019. Based on the results, this paper developed design modification plans for the selected five houses aiming to remediate the health burden the residents are currently facing, and created a design modification matrix that can assist in the decision-making process. The results showed that Kampung houses were suffered from severe dampness and mould risks. TSP and PM2.5 were also alarmingly high. The best options to remediate those are the use of exhaust fans, together with the use of proper finishing materials, i.e. water-resistant materials and mould-resistant paint, using shading devices to improve the indoor comfort on hot days and the change of occupants' behaviour so that the residents adopt more sustainable daily behaviours.